PENGENALANAN KARAKTER MANDARIN DENGAN BACKPROPAGATION DAN EKSTRAKSI CIRI DENGAN GLOBAL HISTOGRAM - Michael Simon (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Mandarin are the second language in the world, after English. Mandarin more difficult to study because of kanji mandarin have so many rules and many lines. Spoken mandarin are difficult too because when we speak example ‘Wo’, there was 4 kind of meaning because mandarin have 4 kind of sound. Today I built a application that can help us to practice mandarin. Key wordsSmoothing Gaussian Filter, Backpropagatiion Neural Network, Global Histogram